2022
DOI: 10.1093/jn/nxac027
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharide Compositions Illustrate Global Variations in Early Nutrition

Abstract: Background Human milk oligosaccharides (HMOs) are an abundant class of compounds found in human milk and have been linked to the development of the infant and specifically the brain, immune system, and gut microbiome. Objectives Advanced analytical methods were used to obtain relative quantitation of many structures in approximately 2000 samples from over 1000 mothers in urban, semi-rural and rural sites across geographically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
4
19
0
Order By: Relevance
“…Precisely, a high index of food insecurity was associated with lower levels of fatty-acids, amino acids, retinol, and the majority of the HMO measured in HM. This is in agreement with the results found by Vinjamuri et al ( 48 ), who found that HM from mothers living in countries with a low GDP per capita had lower HMO levels in 2,000 HM samples from over 1,000 mothers in geographically diverse countries.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Precisely, a high index of food insecurity was associated with lower levels of fatty-acids, amino acids, retinol, and the majority of the HMO measured in HM. This is in agreement with the results found by Vinjamuri et al ( 48 ), who found that HM from mothers living in countries with a low GDP per capita had lower HMO levels in 2,000 HM samples from over 1,000 mothers in geographically diverse countries.…”
Section: Discussionsupporting
confidence: 93%
“…As found in other HM cohort analyses, total HMO levels decreased significantly during the first 6 months of lactation (48,49,56,64,(75)(76)(77). 3-FL was the only HMO found to significantly increase during the first 6 month after birth, which is in line with findings in European and Asian HM cohorts (39,66,67,75).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The diversity of lactation across mammalia is an important asset, so the goal of the IMGC was to assemble a variety of entire genomes from marsupials to humans (6). Comparing these genomes formed the basis for interpreting the evolution of mammalian lactation (7), the expression of genes during lactation (8), the sequences (9) and digestibility of proteins (10), the sequences of peptides (11) and their formation (12), the biosynthetic pathways of glycans ( 13), the variation among women due to genetic diversity (14), timing of lactation (15), diet ( 16) and the biosynthesis of lipids (17).…”
Section: Toolsets Lactation Genomicsmentioning
confidence: 99%
“…Glycan structures are both free and bonded to proteins, peptides or lipids again by enzymatic synthesis. Every glycan, in each sample, must be explicitly analyzed to be identified (14).…”
Section: Milk Oligosaccharides and The Perplexing Lack Of Digestionmentioning
confidence: 99%